They come from across the world - New, Straits Times (New Straits Times, 2014)
AeU held its 4th convocation ceremony at PWTC, Kuala Lumpur. Around 1200 has received their scrolls. The Convocation was graced by ambassadors and representatives from foreign embassies particularly from the 33 ACD countries. The highlights at the graduation ceremony was conferment of PhD of Minister of Education Republic of Namibia.